Trade Unions, Lisbon and Europe 2020: From Dream to Nightmare - Richard Hyman (London School of Economics and Political Science (LSE), European Institute, 2011)
On 24 November 2009 the European Commission published its consultation paper on the EU 2020 strategy. This paper analyses European trade union responses, and contrasts the very limited participation in the exercise with the greater response to the Green Paper Modernising Labour Law three years earlier. It argues that a key explanation is growing trade union disenchantment with the evolution of the 2000 Lisbon Strategy – embraced remarkably uncritically at the time – as it developed over the subsequent decade. In effect, the neoliberal implications of European integration have become increasingly unencumbered by any pretence at a 'social dimension'. It is far from clear that trade unions have as yet a strategy to respond to the far harsher European policy environment.
Keywords: 330